Rubber Exploitation System and Its Influence on Tapping Panel Dryness Disease (Case Study: PT Perkebunan Nusantara XII Kebun Kotta Blater) - Dwi Lestari; Endang Triwahyu Prasetyawati (Nusantara Science and Technology Proceedings, 2022)
Rubber (Hevea brasiliensis Muell Arg.) is one of the main commodities in the plantation sector in Indonesia, making demand for rubber increases every year. The higher the demand for natural rubber, the higher the level of rubber production. Rubber productivity can be maximized through the application of exploitation systems in the field. The exploitation system is a series of tapping systems that are applied throughout the production time of rubber plants (20-25 years) with the aim of obtaining high production yields, and are divided into 2, namely conventional exploitation and stimulants. The application of an excessive rubber exploitation system can cause Tapping Panel Dryness (KAS) disease which is characterized by not releasing latex or drying latex. This research was carried out on January 10 – February 12, 2022 at PT Perkebunan Nusantara XII Kebun Kotta Blater, Jember Regency which aims to determine the effect of the exploitation system on KAS. KAS is influenced by all stages in the exploitation system such as the use of stimulants, plant age, and tapping techniques. The intensity of KAS disease in old rubber TM in 1995 and 1996 was 1-2,20%, while in young rubber TM in 2013 it was 0%. The older the age of the rubber plant, the more susceptible it is to CAS disease as a result of tapping with high intensity (over exploitation), excessive stimulants, or tapping techniques that are not in accordance with the norm, causing wood injuries.